Integral Inequalities Using Generalized Convexity Property Pertaining to Fractional Integrals and Their Applications - Muhammad Talha; Artion Kashuri; Soubhagya Sahoo (Sahand Communications in Mathematical Analysis)
In this study, we established the Hermite-Hadamard type, Simpson type, Ostrowski type and midpoint type integral inequalities for the s-convex functions in the second sense via Katugampola fractional integrals. By using Katugampola fractional integral operators, we obtained several new identities and presented new results for the s-convex function in the second sense. We made connections of our results with various results recognized in the literature. Finally, applications to special means are examined to verify the efficiency of the established results.